(untitled) (Journal of Computational Mathematics, 2007)
In this paper, we discuss an inverse eigenvalue problem for constructing a 2n× 2n Jacobi matrix T such that its 2n eigenvalues are given distinct real values and its leading principal submatrix of order n is a given Jacobi matrix. A new sufficient and necessary condition for the solvability of the above problem is given in this paper. Furthermore, we present a new algorithm and give some numerical results.